Projections from the central amygdaloid nucleus to the precuneiform nucleus in the mouse - Liang, H.; Watson, Charles; Paxinos, G. (Springer, 2013)
The mouse precuneiform nucleus has been proposed as the midbrain locomotion center, a function ascribed to its caudal neighbor, cuneiform nucleus, in the rat, cat and other species. The present study investigated the projections from the central amygdaloid nucleus to the precuneiform nucleus in the mouse using retrograde tracer injections (fluoro-gold) into the precuneiform nucleus and anterograde tracer injections (biotinylated dextran amine) into the central amygdaloid nucleus. The entire central amygdaloid nucleus except the rostral pole had retrogradely labeled neurons, especially in the middle portion where labeled neurons were densely packed. Anterogradely labeled amygdaloid fibers approached the precuneiform nucleus from the area ventrolateral to it and terminated in the entire precuneiform nucleus. Labeled fibers were also found in laminae 5 and 6 in the upper cervical cord on the ipsilateral side. The present study is the first demonstration of projections from the central amygdaloid nucleus to the precuneiform nucleus. This projection may underpin the role of the precuneiform nucleus in the modulation of the cardiovascular activity.